Sistem Informasi Manajemen Inventaris Berbasis Web Di Panada Coffee Menggunakan Metode Rapid Application Development - Restu Kusuma, Rangga; Maulana, Haisyam; Dwicahya Supriatman, Rian (Jurnal Mahasiswa Sistem Informasi Galuh, 2025)
For small and medium-sized businesses (SMEs) such as cafes, technological advances, particularly the internet and web-based applications, offer solutions for inventory management. Currently, Panada Coffee still uses a manual system, which causes many problems, including recording errors, product tracking issues, and miscommunication. Consequently, it is recommended to use the Rapid Application Development (RAD) method to build a “Web-Based Inventory Management Information System.” The RAD method was chosen because it is flexible and accessible anywhere, and allows rapid development according to the specific needs of cafe owners through direct involvement. The purpose of this study is to design and build a web-based inventory management information system for Panada Coffee. This system will have a user-friendly user interface and aims to reduce errors and data loss. Ultimately, this research is expected to help improve accuracy and speed in the entire inventory management process, from data collection, stock management, requests, repairs, to the management of incoming and outgoing goods. The authors used three methods to collect data. First, interviews to obtain further information. Second, conducted documentation by analyzing previous records, such as inventory reports. Finally, they studied literature by reading relevant journals to understand theories and compare research results. This research replaces the manual system with a web-based inventory management information system at Panada Coffee. The researchers recommend developing a system with integration with finance and sales.